Review of Stefano Ballerio (edited by), Morale della fabula (Biblion, 2023) (ENTHYMEMA, 2024)
Review of Stefano Ballerio (edited by),  Morale della fabula. Biblion, 2023.
Keywords: Narratology; Ethics; Morality; Narrative Forms; Novel